The Impact of Motivation and Foreign Language Anxiety on Speaking Performance of Prospective English Teachers - Pande Agus Adiwijaya (Universitas Pendidikan Ganesha, 2021)
This study aims to investigate the impact of motivation and foreign language anxiety (FLA) on the speaking performance of prospective English teachers at one of Indonesia's universities of education. This study is an associational research using multiple linear regression analysis. The participants in this study were students who took Speaking Course I and 67 students were selected as the sample. All data in this study were collected using AMTB & FLCAS questionnaires and speaking tests. The results showed that most of the students had high motivation and FLA in Speaking Course I. In addition, the results showed that FLCAS and AMTB had high motivation and FLA. In addition, the results showed that F (df1=2, df2=64) = 4.080, p < 0.05 which means that motivation and FLA affect students' speaking performance with adjusted R2 = 0.085. Both variables statistically contribute to speaking performance as indicated by t(AMTB) = 2.028, p < 0.05 and t(FLCAS) = -2.580, p < 0.05.